Processing technology of special flexible power supply aluminum alloy cable
Patent Information
- Application Number
- CN202611460355.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-20
- Publication Date
- 2026-10-23
AI Technical Summary
目前市售聚氯乙烯护套电缆普遍存在低温脆性大、反复弯折易开裂、填料与基体相容性差等问题,难以满足长期动态使用需求;而传统铝合金导体晶粒粗大、内应力残留,弯曲疲劳寿命短,易在频繁弯折中发生断裂,制约了电缆的可靠性与使用寿命
本发明的一种特种柔软电源铝合金电缆的加工工艺,通过将柔软铝合金导体安装在放线架上,经预热后,用挤出机将绝缘颗粒包覆在导体上形成绝缘线芯,冷却后将两根绝缘线芯并拢,填入柔性填充绳并在缆芯外层绕包聚酯带,再将烘干后的柔软护套颗粒经挤出机包覆在缆芯外层,护套成型冷却后收卷,放置定型后得到特种柔软电源铝合金电缆;柔软护套颗粒可显著提升电缆护套的柔韧性、耐曲折性与加工稳定性,使电缆更柔软耐用、适配频繁弯折工况;柔软铝合金导体兼具优异导电性、高强度与高柔软性,弯曲不易断裂,可大幅提升电缆使用寿命与移动使用安全性;特种柔软电源铝合金电缆兼具优异的导电性能、高柔软耐弯折性、良好力学强度与低温稳定性,可满足频繁移动弯折工况下的长期可靠使用需求。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of special flexible power aluminum alloy cables, and more specifically to a processing technology for special flexible power aluminum alloy cables. Background Technology
[0002] Special flexible power aluminum alloy cables are widely used in applications involving frequent bending and movement, such as robots, mobile devices, and new energy vehicles. This places extremely high demands on the flexibility, flexural life, and low-temperature toughness of the cable sheath. Currently, commercially available PVC-sheathed cables generally suffer from high low-temperature brittleness, easy cracking after repeated bending, and poor compatibility between the filler and the matrix, making them unsuitable for long-term dynamic use. Meanwhile, traditional aluminum alloy conductors have coarse grains, residual internal stress, and short bending fatigue life, making them prone to breakage during frequent bending, thus limiting the reliability and service life of the cables.
[0003] Existing modification technologies mostly use single plasticizers or elastomers to modify polyvinyl chloride. Although this can improve flexibility to a certain extent, it can easily lead to a decrease in the mechanical strength of the material and a deterioration in its aging resistance. As for aluminum alloy conductors, conventional Al-Ti-B refining processes cannot achieve ultra-fine grains and sufficient elimination of internal stress, resulting in limited improvement in flexibility.
[0004] Therefore, developing a polyvinyl chloride sheath that combines high flexibility, long bending life, and excellent low-temperature toughness with an aluminum alloy conductor that has high conductivity and high resistance to bending fatigue has become a technical challenge that urgently needs to be solved in the field of special flexible power cables, and is of great significance to promoting the localization of cables for high-end equipment. Summary of the Invention
[0005] In order to overcome the above-mentioned technical problems, the purpose of this invention is to provide a processing technology for a special flexible power aluminum alloy cable.
[0006] The objective of this invention can be achieved through the following technical solutions: This application provides a processing technology for a special flexible power aluminum alloy cable, including the following steps: Install the flexible aluminum alloy conductor on the pay-off frame, adjust the pay-off tension to ensure stability and prevent shaking, then start conductor preheating, controlling the temperature at 60-80℃. Add insulating granules to the extruder hopper, using a three-stage extrusion temperature setting: zone one temperature 135-145℃, zone two temperature 145-155℃, and die head temperature 150-160℃. Adjust the die concentricity to ensure the insulation layer covers the conductor, controlling the traction speed at 6-8 m / min. Cool the insulated core in a water-cooling bath at 20-35℃ to obtain the insulated core. Then, join two insulated cores together, filling the gap with flexible filler rope, and then apply insulation to the outer layer of the cable core. Polyester tape is used for overlapping wrapping, with an overlap rate of 30-40%. The soft sheath granules are then dried at 60-70℃ for 2-4 hours. They are then added to an extruder, with the sheath extrusion temperature set as follows: Zone 1 temperature 140-150℃, Zone 2 temperature 150-160℃, and die head temperature 155-165℃. A semi-extrusion die is used, and the traction speed is controlled at 5-7 m / min. After the sheath is formed, it is first rinsed with warm water and then with cold water. Finally, it is wound and shaped, with the winding tension controlled at 10-15 N. After the cable is wound, it is left to set for 24 hours to obtain a special soft power aluminum alloy cable.
[0007] In a preferred embodiment of the present invention, the insulating particles are Dow POE ENGAGE 8150 polyolefin elastomer; the flexible filler rope is made of polypropylene with a diameter of Φ3.0mm; and the polyester wrapping tape has a thickness of 0.05mm.
[0008] In a preferred embodiment of the present invention, the soft sheath particles are prepared by the following steps: Step a1: Add maleic anhydride and n-octadecylamine to a three-necked flask equipped with a stirrer, thermometer and gas delivery tube. Purge with nitrogen for protection. Add toluene using a syringe. Place the three-necked flask in an oil bath and stir for 8-9 hours at a temperature of 75-80℃ and a stirring rate of 300-400 r / min. After the reaction is complete, add the solution dropwise to ice-cold methanol while stirring. Collect the precipitate, filter it using a Buchner funnel, and place the precipitate in a vacuum drying oven. Dry it at a temperature of 45-50℃ for 12-14 hours to obtain octadecylmaleamic acid. Step a2: Add octadecyl maleamic acid and anhydrous sodium acetate to a three-necked flask equipped with a stirrer, thermometer and gas delivery tube. Purge with nitrogen for protection. Add toluene and acetic anhydride separately using a syringe. Then place the three-necked flask in an oil bath and stir for 4-5 hours at 120-130℃ and a stirring rate of 300-400 r / min. Cool to room temperature and add the reaction solution dropwise to ice-cold methanol while stirring. A precipitate will form. Filter the precipitate using a Buchner funnel and place it in a vacuum drying oven. Dry at 55-60℃ for 12-14 hours to obtain N-octadecyl maleimide. Step a3: Add ethylene-vinyl acetate copolymer, N-octadecyl maleimide, and benzoyl peroxide to a three-necked flask equipped with a stirrer, thermometer, and gas delivery tube. Purge with nitrogen for protection. Add toluene using a syringe. Place the three-necked flask in an oil bath and stir for 20-25 minutes at 25-30°C and a stirring rate of 300-400 r / min. Raise the temperature to 75-80°C and continue stirring for 3-4 hours. Add the reacted solution dropwise to ice-cold methanol while stirring to produce a precipitate. Filter the precipitate using a Buchner funnel. Wash the filter cake three times with anhydrous ethanol and then place it in a vacuum drying oven at 45-50°C for 24-26 hours to obtain a high-performance functional modifier. Step a4: Add polyvinyl chloride resin and calcium-zinc stabilizer to a high-speed mixer and mix for 3-4 minutes at a temperature of 75-80℃ and a speed of 700-800 r / min. Add dioctyl terephthalate and dioctyl adipate and continue mixing for 5-6 minutes. Add nitrile rubber and high-performance functional modifier and continue mixing for 4-5 minutes. Add lubricant, antioxidant and activated calcium carbonate and mix for 3-4 minutes. Discharge to obtain the compound material. Step a5: Set the temperature of each section of the twin-screw extruder: section 1 of the die body 130℃, section 2 of the die body 140℃, section 3 of the die body 150℃, and the die head 165℃. Preheat for 30-35 minutes. Add the mixed material to the extruder feed inlet and adjust the screw speed to 25-45 r / min. After the extruded strip is cooled to room temperature in a cooling water tank, it is sent to a pelletizer to be pelletized (particle size 2-3 mm). Collect the pellets and place them in an oven at 60-70℃ to dry for 30-35 minutes to obtain soft-coated pellets.
[0009] In a preferred embodiment of the present invention, the ratio of maleic anhydride, n-octadecylamine and toluene in step a1 is 0.05-0.10 mol: 0.04-0.08 mol: 100-200 mL: 1-2 L.
[0010] In a preferred embodiment of the present invention, the ratio of octadecyl maleic acid, anhydrous sodium acetate, toluene, acetic anhydride and icy methanol in step a2 is 0.04-0.08 mol: 3-6 g: 100-200 mL: 0.15-0.30 mol: 500-1000 mL.
[0011] In a preferred embodiment of the present invention, the ratio of the amount of ethylene-vinyl acetate copolymer, N-octadecyl maleimide, benzoyl peroxide, toluene and icy methanol used in step a3 is 0.5-1.0g: 0.8-1.6g: 0.005-0.02g: 25-50mL: 500-1000mL.
[0012] In a preferred embodiment of the present invention, the ratio of polyvinyl chloride resin, calcium-zinc stabilizer, dioctyl terephthalate, dioctyl adipate, nitrile rubber, high-performance functional modifier, lubricant, antioxidant, and activated calcium carbonate in step a4 is 100-200g: 3.5-7.0g: 35-70mL: 8-16mL: 10-20g: 3-6g: 1.2-2.4g: 0.3-0.6g: 20-40g.
[0013] In a preferred embodiment of the present invention, the polyvinyl chloride resin in step a4 is designated as Zhongtai SG-5; the nitrile rubber is from Lanzhou Petrochemical and is designated as N41E; and the antioxidant is designated as Irganox 1010.
[0014] In a preferred embodiment of the present invention, the lubricant in step a4 is a mixture of low-density polyethylene wax and stearic acid in a ratio of 2:1; the low-density polyethylene wax is BASF, model Luwax® APowder.
[0015] In a preferred embodiment of the present invention, the calcium carbonate in step a4 is 1250 mesh activated calcium carbonate.
[0016] In a preferred embodiment of the present invention, the flexible aluminum alloy conductor is prepared by the following steps: Step b1: Place the graphite crucible in the resistance furnace and preheat it at 300℃ for 30-32 minutes. Then, add the high-purity aluminum ingot to the graphite crucible and put it into the resistance furnace. Heat it to 730℃ at a heating rate of 5℃ / min and hold it for 10-12 minutes. Turn on the argon gas cylinder and insert the argon gas tube 2-3 cm below the surface of the aluminum liquid. Adjust the argon gas flow rate to 0.5L / min and continue blowing argon for 5 minutes. Stop blowing argon and sprinkle the refining agent into it. Stir with a graphite stirring rod for 5-6 minutes. Let it stand for 3-4 minutes and skim off the surface scum to obtain the aluminum liquid. Step b2: Stabilize the temperature of the molten aluminum at 740℃, add the Al-Zr master alloy to the molten aluminum, stir with a graphite stirring rod for 3-4 minutes, let stand for 2-3 minutes, then add the Al-RE rare earth master alloy, stir for 4-5 minutes, let stand for 5-6 minutes, sprinkle the Al-Ti-B refining agent onto the surface of the molten aluminum, stir for 3-4 minutes, let stand for 3-4 minutes, skim off the surface scum, turn on the argon gas again at a flow rate of 0.3L / min, blow argon for 3-4 minutes, then adjust the temperature to 735℃, hold for 2-3 minutes, then pour into a graphite mold, control the casting height at 10-15cm, let the mold cool naturally to room temperature, after cooling, remove the surface oxide layer and burrs to obtain the aluminum alloy ingot; Step b3: Cut the aluminum alloy ingot into φ12mm round bars with a length of 1000mm. Grind the surface with sandpaper, and then cold draw it using a wire drawing machine. Select a wire drawing die with progressively smaller sizes, namely 12mm, 10mm, 8mm, 6mm, and 4mm. Control the deformation amount of each pass to 15-20%, and the total deformation amount to reach 75%. The final wire diameter is φ4mm. After every two passes, wipe the surface of the wire with anhydrous ethanol. Place the cold-drawn wire into an annealing furnace, keeping a gap (≥5mm) between the wires. Close the furnace door and heat it to 300℃ at a heating rate of 3℃ / min. Hold it at this temperature for 1.5-1.7h, and introduce argon gas at a flow rate of 0.2L / min during the process. After annealing, cool it to room temperature with the furnace and grind the surface with sandpaper to obtain a soft aluminum alloy conductor.
[0017] In a preferred embodiment of the present invention, the ratio of high-purity aluminum ingot to refining agent in step b1 is 1000-2000g: 3-5g.
[0018] In a preferred embodiment of the present invention, the high-purity aluminum ingot in step b1 is a 500g piece.
[0019] In a preferred embodiment of the present invention, the refining agent in step b1 is a sodium-free refining agent for aluminum, model: HY-WJ1, with a particle size of 100-200 mesh.
[0020] In a preferred embodiment of the present invention, the ratio of the Al-Zr master alloy, Al-RE rare earth master alloy and Al-Ti-B refining agent in step b2 is 50-100g: 20-40g: 30-60g.
[0021] In a preferred embodiment of the present invention, the Al-Zr master alloy, Al-RE rare earth master alloy, and Al-Ti-B refining agent in step b2 are particles with a diameter of 5-10 mm; the Al-Zr master alloy has a Zr content of 10% and the remainder is Al; the Al-RE rare earth master alloy has a La and Ce mixed rare earth content of 20%, wherein the mass ratio of La to Ce is 1:1 and the remainder is Al; the Al-Ti-B refining agent has a Ti content of 5%, a B content of 1%, and the remainder is Al.
[0022] The beneficial effects of this invention are: This invention discloses a processing technology for a special flexible power aluminum alloy cable. The process involves mounting a flexible aluminum alloy conductor on a pay-off frame, preheating it, and then using an extruder to coat the conductor with insulating particles to form an insulated core. After cooling, two insulated cores are joined together, filled with flexible filler rope, and polyester tape is wrapped around the outer layer of the core. Then, dried flexible sheath particles are extruded onto the outer layer of the core. After the sheath is formed and cooled, it is wound up and set to obtain the special flexible power aluminum alloy cable. The flexible sheath particles significantly improve the flexibility, bending resistance, and processing stability of the cable sheath, making the cable more flexible, durable, and suitable for frequent bending conditions. The flexible aluminum alloy conductor combines excellent conductivity, high strength, and high flexibility, making it less prone to breakage during bending, thus greatly improving the cable's service life and safety during mobile use. The special flexible power aluminum alloy cable combines excellent conductivity, high flexibility and bending resistance, good mechanical strength, and low-temperature stability, meeting the long-term reliable use requirements under frequent bending conditions.
[0023] In the preparation of special flexible power aluminum alloy cables, a flexible sheathing particle was first prepared. Maleic anhydride and n-octadecylamine under a toluene system and nitrogen protection underwent an acylation ring-opening reaction. The anhydride ring of maleic anhydride added to the amino group of n-octadecylamine to generate octadecylmaleamic acid. Then, under anhydrous sodium acetate catalysis and with acetic anhydride as a dehydrating agent, octadecylmaleamic acid underwent an intramolecular dehydration cyclization reaction to form a stable five-membered ring imide structure, yielding N-octadecylmaleimide. Subsequently, using benzoyl peroxide as a free radical initiator, it was decomposed under heating conditions. Free radicals are generated, which abstract active hydrogen from the molecular chain of ethylene-vinyl acetate copolymer to form polymer macromolecular free radicals. These free radicals undergo a free radical graft copolymerization reaction with the carbon-carbon double bond of N-octadecyl maleimide, grafting long-chain alkyl and imide polar groups onto the ethylene-vinyl acetate copolymer backbone. This yields a high-performance functional modifier with excellent compatibility and toughening enhancement with polyvinyl chloride resin. Subsequently, the high-performance functional modifier, nitrile rubber, and polyvinyl chloride resin matrix are fully compatible under high temperature and high shear conditions. Plasticizers, stabilizers, lubricants, and activated calcium carbonate are uniformly dispersed. After screw extrusion and granulation, soft sheath granules with excellent comprehensive performance are obtained. The long-chain alkyl groups in the N-octadecyl maleimide structure can significantly improve the compatibility with the polyvinyl chloride resin system, reduce interfacial tension, and improve the bonding state between inorganic fillers and organic matrix, making the sheath material softer and more resistant to bending. The ethylene-vinyl acetate copolymer graft structure has both polarity and flexibility, which can greatly improve the low-temperature toughness, tensile elongation, and repeated bending life of the polyvinyl chloride resin sheath, making it particularly suitable for flexible power cables. The synergistic effect of nitrile rubber and high-performance functional modifiers can enhance the material's elasticity and resistance. The material exhibits excellent properties, making the sheath less prone to cracking and stress whitening under frequent bending and movement conditions. A high-performance functional modifier, prepared through controlled acylation ring-opening, dehydration cyclization, and free radical grafting reactions, combines the good compatibility of long-chain alkyl groups with the flexibility of ethylene-vinyl acetate copolymers. This effectively improves the interfacial bonding state of the PVC resin matrix, significantly enhancing the softness, bending resistance, and low-temperature toughness of the sheath material. The resulting soft sheath particles possess excellent overall performance, meeting the high-end requirements of special flexible power aluminum alloy cables for sheath softness, toughness, and processability.
[0024] In the process of preparing special flexible power aluminum alloy cables, a flexible aluminum alloy conductor was produced. First, Al-Zr master alloy, Al-RE rare earth master alloy, and Al-Ti-B grain refiner were sequentially added to the molten aluminum to create a synergistic modification effect. Zr element inhibits aluminum alloy recrystallization, refines grains, and improves the material's heat resistance. The mixed rare earth elements La and Ce purify the molten aluminum, remove harmful impurities, and improve the alloy's toughness and processing performance. The Al-Ti-B grain refiner significantly refines the aluminum alloy grains, breaks the columnar crystal structure, forms uniform and fine equiaxed crystals, reduces material brittleness, and ultimately obtains a highly flexible conductor. High-strength aluminum alloy conductor; the purity of the flexible aluminum alloy conductor is controllable. Through the dual action of argon bottom blowing and refining agent purification, gases and impurities in the aluminum liquid are effectively removed, internal defects in the conductor are reduced, and the conductivity and mechanical stability of the conductor are improved. The reasonable combination of Zr, RE rare earth, and Ti-B elements not only refines the grains and reduces the brittleness of the material, but also improves the toughness and fatigue resistance of the conductor, preventing the conductor from breaking during bending. The prepared conductor surface is smooth, free of oxide layer and burrs, and has good bonding with the insulation layer and sheath, which can effectively improve the overall service life and safety of the special flexible power aluminum alloy cable. Detailed Implementation
[0025] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0026] Example 1: This embodiment describes a processing technology for a special flexible power aluminum alloy cable, including the following steps: Step s1: Add 0.05 mol maleic anhydride and 0.04 mol n-octadecylamine to a three-necked flask equipped with a stirrer, thermometer and gas delivery tube. Purge with nitrogen for protection. Add 100 mL of toluene using a syringe. Place the three-necked flask in an oil bath and stir for 8 h at 75 °C and a stirring rate of 300 r / min. After the reaction is complete, add the solution dropwise to 1 L of ice-cold methanol and stir. Collect the precipitate, filter it with a Buchner funnel, and place the precipitate in a vacuum drying oven. Dry it at 45 °C for 12 h to obtain octadecyl maleamic acid. Step s2: Add 0.04 mol octadecyl maleamic acid and 3 g anhydrous sodium acetate to a three-necked flask equipped with a stirrer, thermometer and gas delivery tube. Purge with nitrogen for protection. Add 100 mL toluene and 0.15 mol acetic anhydride using a syringe. Then place the three-necked flask in an oil bath and stir for 4 h at 120 °C and 300 r / min. Cool to room temperature and add the reaction solution dropwise to 500 mL of ice-cold methanol while stirring. A precipitate is formed. Filter the precipitate using a Buchner funnel and place it in a vacuum drying oven. Dry at 55 °C for 12 h to obtain N-octadecyl maleimide. Step s3: Add 0.5g of ethylene-vinyl acetate copolymer, 0.8g of N-octadecyl maleimide, and 0.005g of benzoyl peroxide to a three-necked flask equipped with a stirrer, thermometer, and gas delivery tube. Purge with nitrogen for protection. Add 25mL of toluene using a syringe. Place the three-necked flask in an oil bath and stir for 20min at 25℃ and a stirring rate of 300r / min. Increase the temperature to 75℃ and continue stirring for 3h. Add the reacted solution dropwise to 500mL of ice-cold methanol and stir to produce a precipitate. Filter the precipitate using a Buchner funnel. Wash the filter cake three times with anhydrous ethanol and then place it in a vacuum drying oven at 45℃ for 24h to obtain a high-performance functional modifier. Step s4: Add 100g of polyvinyl chloride resin (polyvinyl chloride resin product number: Zhongtai SG-5) and 3.5g of calcium-zinc stabilizer to a high-speed mixer and mix for 3 minutes at 75℃ and 700r / min. Add 35mL of dioctyl terephthalate and 8mL of dioctyl adipate and continue mixing for 5 minutes. Add 10g of nitrile rubber (nitrile rubber is Lanzhou Petrochemical, model: N41E) and 3g of high-performance functional modifier and continue mixing for 4 minutes. Add 1.2g of lubricant (lubricant is a mixture of low-density polyethylene wax and stearic acid in a 2:1 ratio; low-density polyethylene wax is BASF, model: Luwax® A Powder), 0.3g of antioxidant (antioxidant model: Irganox 1010), and 20g of activated calcium carbonate (calcium carbonate is 1250 mesh activated calcium carbonate). Mix for 3 minutes and discharge to obtain the compound material. Step s5: Set the temperature of each section of the twin-screw extruder: section 1 of the die body 130℃, section 2 of the die body 140℃, section 3 of the die body 150℃, and the die head 165℃. Preheat for 30 minutes. Add the mixed material to the feed port of the extruder. Adjust the screw speed to 25 r / min. After the extruded strip is cooled to room temperature in a cooling water tank, it is sent to a pelletizer to be pelletized (particle size 2mm). Collect the pellets and place them in an oven at 60℃ to dry for 30 minutes to obtain soft sheathed pellets. Step s6: Place the graphite crucible in the resistance furnace and preheat it at 300℃ for 30 minutes. Then, add 1000g of high-purity aluminum ingot (500g small pieces) to the graphite crucible and place it in the resistance furnace. Heat the crucible to 730℃ at a heating rate of 5℃ / min and hold it for 10 minutes. Turn on the argon gas cylinder and insert the argon gas tube 2cm below the surface of the molten aluminum. Adjust the argon gas flow rate to 0.5L / min and continue blowing argon for 5 minutes. Stop blowing argon and sprinkle 3g of refining agent (sodium-free refining agent for aluminum, model: HY-WJ1, particle size: 100 mesh) into the crucible. Stir with a graphite stirring rod for 5 minutes, let it stand for 3 minutes, and skim off the surface scum to obtain molten aluminum. Step s7: Stabilize the temperature of the molten aluminum at 740℃. Add 50g of Al-Zr master alloy (10% Zr content, the remainder being Al, 5mm diameter) to the molten aluminum and stir with a graphite stirring rod for 3 minutes. Let it stand for 2 minutes. Then add 20g of Al-RE rare earth master alloy (20% La and Ce mixed rare earth content, where the mass ratio of La to Ce is 1:1, the remainder being Al, 5mm diameter). Stir for 4 minutes and let it stand for 5 minutes. Sprinkle 30g of Al-Ti-B refining agent (5% Ti content, 1% B content, the remainder being Al, 5mm diameter) onto the surface of the molten aluminum and stir for 3 minutes. Let it stand for 3 minutes. Skim off the surface scum. Turn on the argon gas again at a flow rate of 0.3L / min and blow argon for 3 minutes. Then adjust the temperature to 735℃ and hold for 2 minutes. Then pour it into a graphite mold and control the casting height at 10cm. Let the mold cool naturally to room temperature. After cooling, remove the surface oxide layer and burrs to obtain the aluminum alloy ingot. Step s8: Cut the aluminum alloy ingot into φ12mm round bars with a length of 1000mm. Polish the surface with sandpaper, and then cold draw it using a wire drawing machine. Select a wire drawing die with progressively smaller sizes, with the die sizes being 12mm, 10mm, 8mm, 6mm, and 4mm respectively. Control the deformation amount in each pass to 15%, and the total deformation amount to reach 75%. The final wire diameter is φ4mm. After every two passes, wipe the surface of the wire with anhydrous ethanol. Place the cold-drawn wire into an annealing furnace, maintaining a gap (≥5mm) between the wires. Close the furnace door and heat it to 300℃ at a heating rate of 3℃ / min. Hold it at this temperature for 1.5h, during which argon gas with a flow rate of 0.2L / min is introduced. After annealing, cool it to room temperature with the furnace and polish the surface with sandpaper to obtain a soft aluminum alloy conductor. Step s9: Install the flexible aluminum alloy conductor on the pay-off frame, adjust the pay-off tension to be stable and without shaking, then turn on the conductor preheating, controlling the temperature at 60℃. Add the insulating granules (Dow POE ENGAGE 8150 polyolefin elastomer) to the extruder hopper, using a three-stage extrusion temperature setting: zone 1 temperature 135℃, zone 2 temperature 145℃, and die head temperature 150℃. Adjust the die concentricity to ensure the insulation layer covers the conductor, controlling the traction speed at 6m / min. Cool the insulated wire core in a water-cooling bath at 20℃ to obtain the insulated wire core. Then, bring the two insulated wire cores together, filling the gap with flexible filler rope (the flexible filler rope is made of polypropylene with a diameter of Φ3.0mm). Finally, apply polyester tape (the thickness of the polyester wrapping tape is 0mm) to the outer layer of the cable core. The soft sheath particles (0.05mm) are overlapped and wrapped, with an overlap rate of 30%. Then, the soft sheath particles are dried at 60℃ for 2 hours and added to an extruder. The sheath extrusion temperature is set as follows: zone 1 temperature is 140℃, zone 2 temperature is 150℃, and die head temperature is 155℃. A semi-extrusion die is used, and the traction speed is controlled at 5m / min. After the sheath is formed, it is first rinsed with warm water and then with cold water. Finally, it is wound and shaped, with the winding tension controlled at 10N. After the cable is wound, it is placed for 24 hours to shape, resulting in a special soft power aluminum alloy cable.
[0027] Example 2: This embodiment describes a processing technology for a special flexible power aluminum alloy cable, including the following steps: Step s1: Add 0.07.5 mol maleic anhydride and 0.06 mol n-octadecylamine to a three-necked flask equipped with a stirrer, thermometer and gas delivery tube. Purge with nitrogen for protection. Add 150 mL of toluene using a syringe. Place the three-necked flask in an oil bath and stir for 8.5 h at 77 °C and a stirring rate of 350 r / min. After the reaction is complete, add the solution dropwise to 1.5 L of ice-cold methanol and stir. Collect the precipitate, filter it with a Buchner funnel, and place the precipitate in a vacuum drying oven. Dry it at 47 °C for 13 h to obtain octadecylmaleamic acid. Step s2: Add 0.06 mol octadecyl maleamic acid and 4.5 g anhydrous sodium acetate to a three-necked flask equipped with a stirrer, thermometer and gas delivery tube. Purge with nitrogen for protection. Add 150 mL toluene and 0.225 mol acetic anhydride using a syringe. Then place the three-necked flask in an oil bath and stir for 4.5 h at 125 °C and 350 r / min. Cool to room temperature and add the reaction solution dropwise to 700 mL ice-cold methanol while stirring. A precipitate is formed. Filter the precipitate using a Buchner funnel and place it in a vacuum drying oven. Dry at 57 °C for 13 h to obtain N-octadecyl maleimide. Step s3: Add 0.75g of ethylene-vinyl acetate copolymer, 1.2g of N-octadecyl maleimide and 0.01g of benzoyl peroxide to a three-necked flask equipped with a stirrer, thermometer and gas delivery tube. Purge with nitrogen for protection. Add 37.5mL of toluene using a syringe. Place the three-necked flask in an oil bath and stir for 23min at 27℃ and 350r / min. Raise the temperature to 77℃ and continue stirring for 3.5h. Add the reacted solution dropwise to 700mL of ice-cold methanol and stir to produce a precipitate. Filter the precipitate using a Buchner funnel. Wash the filter cake three times with anhydrous ethanol and then place it in a vacuum drying oven and dry at 47℃ for 25h to obtain a high-performance functional modifier. Step s4: Add 150g of polyvinyl chloride resin (polyvinyl chloride resin product number: Zhongtai SG-5) and 5.25g of calcium-zinc stabilizer to a high-speed mixer and mix for 3.5 minutes at 77℃ and 750r / min. Add 52.5mL of dioctyl terephthalate and 12mL of dioctyl adipate, and continue mixing for 5.5 minutes. Add 15g of nitrile rubber (nitrile rubber is from Lanzhou Petrochemical, model N41E) and 4.5g of high-performance functional modifier, and continue mixing for 4.5 minutes. Add 1.8g of lubricant (the lubricant is a mixture of low-density polyethylene wax and stearic acid in a 2:1 ratio; the low-density polyethylene wax is from BASF, model Luwax® A). Powder), 0.45g antioxidant (Irganox 1010) and 30g activated calcium carbonate (1250 mesh activated calcium carbonate) were mixed for 3.5 minutes and discharged to obtain the compound material. Step s5: Set the temperature of each section of the twin-screw extruder: section 1 of the die body 130℃, section 2 of the die body 140℃, section 3 of the die body 150℃, and the die head 165℃. Preheat for 32 minutes. Add the mixed material to the feed port of the extruder and adjust the screw speed to 35 r / min. After the extruded strip is cooled to room temperature in a cooling water tank, it is fed into a pelletizer to be pelletized (particle size 2mm). Collect the pellets and place them in an oven at 65℃ to dry for 32 minutes to obtain soft sheathed pellets. Step s6: Place the graphite crucible in the resistance furnace and preheat it at 300℃ for 31 minutes. Then, add 1500g of high-purity aluminum ingot (500g small pieces) to the graphite crucible and place it in the resistance furnace. Heat the crucible to 730℃ at a heating rate of 5℃ / min and hold it for 11 minutes. Turn on the argon gas cylinder and insert the argon gas tube 2cm below the surface of the molten aluminum. Adjust the argon gas flow rate to 0.5L / min and continue blowing argon for 5 minutes. Stop blowing argon and sprinkle 4g of refining agent (sodium-free refining agent for aluminum, model: HY-WJ1, particle size: 150 mesh) into the crucible. Stir with a graphite stirring rod for 5.5 minutes, let it stand for 3.5 minutes, and skim off the surface scum to obtain molten aluminum. Step s7: Stabilize the aluminum melt temperature at 740℃, add 75g of Al-Zr master alloy (10% Zr content, the remainder is Al, 7mm diameter) to the aluminum melt, stir with a graphite stirring rod for 3.5min, let stand for 2.5min, then add 30g of Al-RE rare earth master alloy (20% La and Ce mixed rare earth content, where La and Ce are mixed rare earth elements). The mass ratio is 1:1, the remainder is Al, and the diameter is 7mm). Stir for 4.5min, let stand for 5.5min, sprinkle 45g of Al-Ti-B refining agent (Ti content 5%, B content 1%, the remainder is Al, diameter 7mm) onto the surface of the aluminum liquid, stir for 3.5min, let stand for 3.5min, skim off the surface scum, turn on the argon gas again at a flow rate of 0.3L / min, blow argon for 3.5min, then adjust the temperature to 735℃, hold for 2.5min, then pour into a graphite mold, control the casting height at 12cm, let the mold cool naturally to room temperature, remove the surface oxide layer and burrs after cooling, and obtain the aluminum alloy ingot; Step s8: Cut the aluminum alloy ingot into φ12mm round bars with a length of 1000mm. Polish the surface with sandpaper, and then cold draw it using a wire drawing machine. Select a wire drawing die with progressively smaller sizes, with the die sizes being 12mm, 10mm, 8mm, 6mm, and 4mm respectively. Control the deformation amount in each pass to 17%, and the total deformation amount to reach 75%. The final wire diameter is φ4mm. After every two passes, wipe the surface of the wire with anhydrous ethanol. Place the cold-drawn wire into an annealing furnace, maintaining a gap (≥5mm) between the wires. Close the furnace door and heat it to 300℃ at a heating rate of 3℃ / min. Hold it at this temperature for 1.6h, during which argon gas with a flow rate of 0.2L / min is introduced. After annealing, cool it to room temperature with the furnace and polish the surface with sandpaper to obtain a soft aluminum alloy conductor. Step s9: Install the flexible aluminum alloy conductor on the pay-off frame, adjust the pay-off tension to be stable and without shaking, then start conductor preheating, controlling the temperature at 70℃. Add the insulating granules (Dow POE ENGAGE 8150 polyolefin elastomer) to the extruder hopper, using a three-stage extrusion temperature setting: zone 1 temperature 140℃, zone 2 temperature 150℃, and die head temperature 155℃. Adjust the die concentricity to ensure the insulation layer covers the conductor, controlling the traction speed at 7m / min. Cool the insulated wire core in a water-cooling bath at 27℃ to obtain the insulated wire core. Then, bring the two insulated wire cores together, filling the gap with flexible filler rope (the flexible filler rope is made of polypropylene with a diameter of Φ3.0mm). Finally, apply polyester tape (the thickness of the polyester wrapping tape is 0mm) to the outer layer of the cable core. The soft sheath particles (0.05mm) are overlapped and wrapped, with an overlap rate of 35%. Then, the soft sheath particles are dried at 65℃ for 3 hours and then added to an extruder. The sheath extrusion temperature is set as follows: zone 1 temperature is 145℃, zone 2 temperature is 155℃, and die head temperature is 160℃. A semi-extrusion die is used, and the traction speed is controlled at 6m / min. After the sheath is formed, it is first warm water and then cold water. Finally, it is wound and shaped, and the winding tension is controlled at 13N. After the cable is wound, it is placed for 24 hours to shape, resulting in a special soft power aluminum alloy cable.
[0028] Example 3: This embodiment describes a processing technology for a special flexible power aluminum alloy cable, including the following steps: Step s1: Add 0.10 mol maleic anhydride and 0.08 mol n-octadecylamine to a three-necked flask equipped with a stirrer, thermometer and gas delivery tube. Purge with nitrogen for protection. Add 200 mL toluene using a syringe. Place the three-necked flask in an oil bath and stir for 9 h at 80 °C and a stirring rate of 400 r / min. After the reaction is complete, add the solution dropwise to 2 L of ice-cold methanol and stir. Collect the precipitate, filter it using a Buchner funnel, and place the precipitate in a vacuum drying oven. Dry it at 50 °C for 14 h to obtain octadecyl maleamic acid. Step s2: Add 0.08 mol octadecyl maleamic acid and 6 g anhydrous sodium acetate to a three-necked flask equipped with a stirrer, thermometer and gas delivery tube. Purge with nitrogen for protection. Add 200 mL toluene and 0.30 mol acetic anhydride using a syringe. Then place the three-necked flask in an oil bath and stir for 5 h at 130 °C and 400 r / min. Cool to room temperature and add the reaction solution dropwise to 1000 mL ice-cold methanol while stirring. A precipitate is formed. Filter the precipitate using a Buchner funnel and place it in a vacuum drying oven. Dry at 60 °C for 14 h to obtain N-octadecyl maleimide. Step s3: Add 1.0g of ethylene-vinyl acetate copolymer, 1.6g of N-octadecyl maleimide and 0.02g of benzoyl peroxide to a three-necked flask equipped with a stirrer, thermometer and gas delivery tube. Purge with nitrogen for protection. Add 50mL of toluene using a syringe. Place the three-necked flask in an oil bath and stir for 25min at 30℃ and 400r / min. Raise the temperature to 80℃ and continue stirring for 4h. Add the reacted solution dropwise to 1000mL of ice-cold methanol and stir to produce a precipitate. Filter the precipitate using a Buchner funnel. Wash the filter cake three times with anhydrous ethanol and then place it in a vacuum drying oven and dry at 50℃ for 26h to obtain a high-performance functional modifier. Step s4: Add 200g of polyvinyl chloride resin (polyvinyl chloride resin product number: Zhongtai SG-5) and 7.0g of calcium-zinc stabilizer to a high-speed mixer and mix for 4 minutes at 80℃ and 800r / min. Add 70mL of dioctyl terephthalate and 16mL of dioctyl adipate and continue mixing for 6 minutes. Add 20g of nitrile rubber (nitrile rubber is Lanzhou Petrochemical, model N41E) and 6g of high-performance functional modifier and continue mixing for 5 minutes. Add 2.4g of lubricant (lubricant is a mixture of low-density polyethylene wax and stearic acid in a 2:1 ratio; low-density polyethylene wax is BASF, model Luwax® A Powder), 0.6g of antioxidant (antioxidant model: Irganox 1010), and 40g of activated calcium carbonate (calcium carbonate is 1250 mesh activated calcium carbonate). Mix for 4 minutes and discharge to obtain the compound material. Step s5: Set the temperature of each section of the twin-screw extruder: section 1 of the die body 130℃, section 2 of the die body 140℃, section 3 of the die body 150℃, and the die head 165℃. Preheat for 35 minutes. Add the mixed material to the feed port of the extruder and adjust the screw speed to 45 r / min. After the extruded strip is cooled to room temperature in a cooling water tank, it is sent to a pelletizer to be pelletized (particle size 3mm). Collect the pellets and place them in an oven at 70℃ to dry for 35 minutes to obtain soft sheathed pellets. Step s6: Place the graphite crucible in the resistance furnace and preheat it at 300℃ for 32 minutes. Then, add 2000g of high-purity aluminum ingot (500g small pieces) to the graphite crucible and place it in the resistance furnace. Heat the crucible to 730℃ at a heating rate of 5℃ / min and hold it for 12 minutes. Turn on the argon gas cylinder and insert the argon gas tube 3cm below the surface of the molten aluminum. Adjust the argon gas flow rate to 0.5L / min and continue blowing argon for 5 minutes. Stop blowing argon and sprinkle 3-5g of refining agent (sodium-free refining agent for aluminum, model: HY-WJ1, particle size: 200 mesh) into the crucible. Stir with a graphite stirring rod for 6 minutes, let it stand for 4 minutes, and skim off the surface scum to obtain molten aluminum. Step s7: Stabilize the temperature of the molten aluminum at 740℃. Add 100g of Al-Zr master alloy (10% Zr content, the remainder is Al, diameter 10mm) to the molten aluminum and stir with a graphite stirring rod for 4 minutes. Let it stand for 3 minutes. Then add 40g of Al-RE rare earth master alloy (20% La and Ce mixed rare earth content, where the mass ratio of La to Ce is 1:1, the remainder is Al, diameter 10mm), stir for 5 minutes, and let it stand for 6 minutes. Sprinkle 60g of Al-Ti-B refining agent (5% Ti content, 1% B content, the remainder is Al, diameter 10mm) onto the surface of the molten aluminum, stir for 4 minutes, let it stand for 4 minutes, skim off the surface scum, turn on the argon gas again at a flow rate of 0.3L / min, blow argon for 4 minutes, then adjust the temperature to 735℃ and hold for 3 minutes. Then pour it into a graphite mold, control the casting height at 15cm, and let the mold cool naturally to room temperature. After cooling, remove the surface oxide layer and burrs to obtain the aluminum alloy ingot. Step s8: Cut the aluminum alloy ingot into φ12mm round bars with a length of 1000mm. Polish the surface with sandpaper, and then cold draw it using a wire drawing machine. Select a wire drawing die with progressively smaller sizes, with the die sizes being 12mm, 10mm, 8mm, 6mm, and 4mm respectively. Control the deformation amount in each pass to 20%, and the total deformation amount to reach 75%. The final wire diameter is φ4mm. After every two passes, wipe the surface of the wire with anhydrous ethanol. Place the cold-drawn wire into an annealing furnace, maintaining a gap (≥5mm) between the wires. Close the furnace door and heat it to 300℃ at a heating rate of 3℃ / min. Hold it at this temperature for 1.7h, during which argon gas with a flow rate of 0.2L / min is introduced. After annealing, cool it to room temperature with the furnace and polish the surface with sandpaper to obtain a soft aluminum alloy conductor. Step s9: Install the flexible aluminum alloy conductor on the pay-off frame, adjust the pay-off tension to be stable and without shaking, then start conductor preheating, controlling the temperature at 80℃. Add the insulating granules (Dow POE ENGAGE 8150 polyolefin elastomer) to the extruder hopper, using a three-stage extrusion temperature setting: zone 1 temperature 145℃, zone 2 temperature 155℃, and die head temperature 160℃. Adjust the die concentricity to ensure the insulation layer covers the conductor, controlling the traction speed at 8m / min. Cool the insulated wire core in a water-cooling bath at 35℃ to obtain the insulated wire core. Then, bring the two insulated wire cores together, filling the gap with flexible filler rope (the flexible filler rope is made of polypropylene with a diameter of Φ3.0mm). Finally, apply polyester tape (the thickness of the polyester wrapping tape is 0mm) to the outer layer of the cable core. The soft sheath particles (0.05mm) are overlapped and wrapped, with an overlap rate of 40%. Then, the soft sheath particles are dried at 70℃ for 4 hours and then added to an extruder. The sheath extrusion temperature is set as follows: zone 1 temperature is 150℃, zone 2 temperature is 160℃, and die head temperature is 165℃. A semi-extrusion die is used, and the traction speed is controlled at 7m / min. After the sheath is formed, it is first rinsed with warm water and then with cold water. Finally, it is wound and shaped, and the winding tension is controlled at 15N. After the cable is wound, it is placed for 24 hours to shape, resulting in a special soft power aluminum alloy cable.
[0029] Comparative Example 1: This comparative example illustrates the processing technology of a special flexible power aluminum alloy cable, including the following steps: Step s1: Add 100g of polyvinyl chloride resin (polyvinyl chloride resin product number: Zhongtai SG-5) and 3.5g of calcium-zinc stabilizer to a high-speed mixer and mix for 3 minutes at a temperature of 75℃ and a speed of 700r / min. Add 35mL of dioctyl terephthalate and 8mL of dioctyl adipate and continue stirring for 5 minutes. Add 10g of nitrile rubber (nitrile rubber is Lanzhou Petrochemical, model: N41E) and continue mixing for 4 minutes. Add 1.2g of lubricant (lubricant is a mixture of low-density polyethylene wax and stearic acid in a 2:1 ratio; low-density polyethylene wax is BASF, model: Luwax® A Powder), 0.3g of antioxidant (antioxidant model: Irganox 1010), and 20g of activated calcium carbonate (calcium carbonate is 1250 mesh activated calcium carbonate). Mix for 3 minutes and discharge to obtain the compound material. Step s2: Set the temperature of each section of the twin-screw extruder: section 1 of the die body 130℃, section 2 of the die body 140℃, section 3 of the die body 150℃, and the die head 165℃. Preheat for 30 minutes. Add the mixed material to the feed port of the extruder and adjust the screw speed to 25 r / min. After the extruded strip is cooled to room temperature in a cooling water tank, it is sent to a pelletizer to be pelletized (particle size 2mm). Collect the pellets and place them in an oven at 60℃ to dry for 30 minutes to obtain soft sheathed pellets. Step s3: Place the graphite crucible in the resistance furnace and preheat it at 300℃ for 30 minutes. Then, add 1000g of high-purity aluminum ingot (500g small pieces) to the graphite crucible and place it in the resistance furnace. Heat the crucible to 730℃ at a heating rate of 5℃ / min and hold it for 10 minutes. Turn on the argon gas cylinder and insert the argon gas tube 2cm below the surface of the molten aluminum. Adjust the argon gas flow rate to 0.5L / min and continue blowing argon for 5 minutes. Stop blowing argon and sprinkle 3g of refining agent (sodium-free refining agent for aluminum, model: HY-WJ1, particle size: 100 mesh) into the crucible. Stir with a graphite stirring rod for 5 minutes, let it stand for 3 minutes, and skim off the surface scum to obtain molten aluminum. Step s4: Stabilize the temperature of the molten aluminum at 740℃. Add 50g of Al-Zr master alloy (10% Zr content, the remainder is Al, diameter 5mm) to the molten aluminum and stir with a graphite stirring rod for 3 minutes. Let it stand for 2 minutes. Then add 20g of Al-RE rare earth master alloy (20% La and Ce mixed rare earth content, where the mass ratio of La to Ce is 1:1, the remainder is Al, diameter 5mm), stir for 4 minutes, and let it stand for 5 minutes. Sprinkle 30g of Al-Ti-B refining agent (5% Ti content, 1% B content, the remainder is Al, diameter 5mm) onto the surface of the molten aluminum, stir for 3 minutes, and let it stand for 3 minutes. Skim off the surface slag, turn on the argon gas again at a flow rate of 0.3L / min, and blow argon for 3 minutes. Then adjust the temperature to 735℃ and hold for 2 minutes. Then pour it into a graphite mold, control the casting height at 10cm, and let the mold cool naturally to room temperature. After cooling, remove the surface oxide layer and burrs to obtain the aluminum alloy ingot. Step s5: Cut the aluminum alloy ingot into φ12mm round bars with a length of 1000mm. Grind the surface with sandpaper, and then cold draw it using a wire drawing machine. Select a wire drawing die with progressively smaller sizes, with the die sizes being 12mm, 10mm, 8mm, 6mm, and 4mm respectively. Control the deformation amount in each pass to 15%, and the total deformation amount to reach 75%. The final wire diameter is φ4mm. After every two passes, wipe the surface of the wire with anhydrous ethanol. Place the cold-drawn wire into an annealing furnace, maintaining a gap (≥5mm) between the wires. Close the furnace door and heat it to 300℃ at a heating rate of 3℃ / min. Hold it at this temperature for 1.5h, during which argon gas with a flow rate of 0.2L / min is introduced. After annealing, cool it to room temperature with the furnace and grind the surface with sandpaper to obtain a soft aluminum alloy conductor. Step s6: Install the flexible aluminum alloy conductor on the pay-off frame, adjust the pay-off tension to be stable and without shaking, then start conductor preheating, controlling the temperature at 60℃. Add the insulating granules (Dow POE ENGAGE 8150 polyolefin elastomer) to the extruder hopper, using a three-stage extrusion temperature setting: zone 1 temperature 135℃, zone 2 temperature 145℃, and die head temperature 150℃. Adjust the die concentricity to ensure the insulation layer covers the conductor, controlling the traction speed at 6m / min. Cool the insulated wire core in a water-cooling bath at 20℃ to obtain the insulated wire core. Then, bring two insulated wire cores together, filling the gap with flexible filler rope (the flexible filler rope is made of polypropylene with a diameter of Φ3.0mm). Finally, apply polyester tape (the thickness of the polyester wrapping tape is 0mm) to the outer layer of the cable core. The soft sheath particles (0.05mm) are overlapped and wrapped, with an overlap rate of 30%. Then, the soft sheath particles are dried at 60℃ for 2 hours and added to an extruder. The sheath extrusion temperature is set as follows: zone 1 temperature is 140℃, zone 2 temperature is 150℃, and die head temperature is 155℃. A semi-extrusion die is used, and the traction speed is controlled at 5m / min. After the sheath is formed, it is first rinsed with warm water and then with cold water. Finally, it is wound and shaped, with the winding tension controlled at 10N. After the cable is wound, it is placed for 24 hours to shape, resulting in a special soft power aluminum alloy cable.
[0030] Comparative Example 2: This comparative example illustrates the processing technology of a special flexible power aluminum alloy cable, including the following steps: Step s1: Add 0.05 mol maleic anhydride and 0.04 mol n-octadecylamine to a three-necked flask equipped with a stirrer, thermometer and gas delivery tube. Purge with nitrogen for protection. Add 100 mL of toluene using a syringe. Place the three-necked flask in an oil bath and stir for 8 h at 75 °C and a stirring rate of 300 r / min. After the reaction is complete, add the solution dropwise to 1 L of ice-cold methanol and stir. Collect the precipitate, filter it with a Buchner funnel, and place the precipitate in a vacuum drying oven. Dry it at 45 °C for 12 h to obtain octadecyl maleamic acid. Step s2: Add 0.04 mol octadecyl maleamic acid and 3 g anhydrous sodium acetate to a three-necked flask equipped with a stirrer, thermometer and gas delivery tube. Purge with nitrogen for protection. Add 100 mL toluene and 0.15 mol acetic anhydride using a syringe. Then place the three-necked flask in an oil bath and stir for 4 h at 120 °C and 300 r / min. Cool to room temperature and add the reaction solution dropwise to 500 mL of ice-cold methanol while stirring. A precipitate is formed. Filter the precipitate using a Buchner funnel and place it in a vacuum drying oven. Dry at 55 °C for 12 h to obtain N-octadecyl maleimide. Step s3: Add 0.5g of ethylene-vinyl acetate copolymer, 0.8g of N-octadecyl maleimide, and 0.005g of benzoyl peroxide to a three-necked flask equipped with a stirrer, thermometer, and gas delivery tube. Purge with nitrogen for protection. Add 25mL of toluene using a syringe. Place the three-necked flask in an oil bath and stir for 20min at 25℃ and a stirring rate of 300r / min. Increase the temperature to 75℃ and continue stirring for 3h. Add the reacted solution dropwise to 500mL of ice-cold methanol and stir to produce a precipitate. Filter the precipitate using a Buchner funnel. Wash the filter cake three times with anhydrous ethanol and then place it in a vacuum drying oven at 45℃ for 24h to obtain a high-performance functional modifier. Step s4: Add 100g of polyvinyl chloride resin (polyvinyl chloride resin product number: Zhongtai SG-5) and 3.5g of calcium-zinc stabilizer to a high-speed mixer and mix for 3 minutes at 75℃ and 700r / min. Add 35mL of dioctyl terephthalate and 8mL of dioctyl adipate and continue mixing for 5 minutes. Add 10g of nitrile rubber (nitrile rubber is Lanzhou Petrochemical, model: N41E) and 3g of high-performance functional modifier and continue mixing for 4 minutes. Add 1.2g of lubricant (lubricant is a mixture of low-density polyethylene wax and stearic acid in a 2:1 ratio; low-density polyethylene wax is BASF, model: Luwax® A Powder), 0.3g of antioxidant (antioxidant model: Irganox 1010), and 20g of activated calcium carbonate (calcium carbonate is 1250 mesh activated calcium carbonate). Mix for 3 minutes and discharge to obtain the compound material. Step s5: Set the temperature of each section of the twin-screw extruder: section 1 of the die body 130℃, section 2 of the die body 140℃, section 3 of the die body 150℃, and the die head 165℃. Preheat for 30 minutes. Add the mixed material to the feed port of the extruder. Adjust the screw speed to 25 r / min. After the extruded strip is cooled to room temperature in a cooling water tank, it is sent to a pelletizer to be pelletized (particle size 2mm). Collect the pellets and place them in an oven at 60℃ to dry for 30 minutes to obtain soft sheathed pellets. Step s6: Place the graphite crucible in the resistance furnace and preheat it at 300℃ for 30 minutes. Then, add 1000g of high-purity aluminum ingot (500g small pieces) to the graphite crucible and place it in the resistance furnace. Heat the crucible to 730℃ at a heating rate of 5℃ / min and hold it for 10 minutes. Turn on the argon gas cylinder and insert the argon gas tube 2cm below the surface of the molten aluminum. Adjust the argon gas flow rate to 0.5L / min and continue blowing argon for 5 minutes. Stop blowing argon and sprinkle 3g of refining agent (sodium-free refining agent for aluminum, model: HY-WJ1, particle size: 100 mesh) into the crucible. Stir with a graphite stirring rod for 5 minutes, let it stand for 3 minutes, and skim off the surface scum to obtain molten aluminum. Step s7: Stabilize the temperature of the molten aluminum at 740℃, sprinkle 30g of Al-Ti-B refining agent (5% Ti content, 1% B content, the remainder is Al, 5mm diameter) onto the surface of the molten aluminum, stir for 3 minutes, let stand for 3 minutes, skim off the surface scum, turn on the argon gas again at a flow rate of 0.3L / min, blow argon for 3 minutes, then adjust the temperature to 735℃, hold for 2 minutes, then pour into a graphite mold, control the casting height at 10cm, let the mold cool naturally to room temperature, remove the surface oxide layer and burrs after cooling, and obtain the aluminum alloy ingot; Step s8: Cut the aluminum alloy ingot into φ12mm round bars with a length of 1000mm. Polish the surface with sandpaper, and then cold draw it using a wire drawing machine. Select a wire drawing die with progressively smaller sizes, with the die sizes being 12mm, 10mm, 8mm, 6mm, and 4mm respectively. Control the deformation amount in each pass to 15%, and the total deformation amount to reach 75%. The final wire diameter is φ4mm. After every two passes, wipe the surface of the wire with anhydrous ethanol. Place the cold-drawn wire into an annealing furnace, maintaining a gap (≥5mm) between the wires. Close the furnace door and heat it to 300℃ at a heating rate of 3℃ / min. Hold it at this temperature for 1.5h, during which argon gas with a flow rate of 0.2L / min is introduced. After annealing, cool it to room temperature with the furnace and polish the surface with sandpaper to obtain a soft aluminum alloy conductor. Step s9: Install the flexible aluminum alloy conductor on the pay-off frame, adjust the pay-off tension to be stable and without shaking, then turn on the conductor preheating, controlling the temperature at 60℃. Add the insulating granules (Dow POE ENGAGE 8150 polyolefin elastomer) to the extruder hopper, using a three-stage extrusion temperature setting: zone 1 temperature 135℃, zone 2 temperature 145℃, and die head temperature 150℃. Adjust the die concentricity to ensure the insulation layer covers the conductor, controlling the traction speed at 6m / min. Cool the insulated wire core in a water-cooling bath at 20℃ to obtain the insulated wire core. Then, bring the two insulated wire cores together, filling the gap with flexible filler rope (the flexible filler rope is made of polypropylene with a diameter of Φ3.0mm). Finally, apply polyester tape (the thickness of the polyester wrapping tape is 0mm) to the outer layer of the cable core. The soft sheath particles (0.05mm) are overlapped and wrapped, with an overlap rate of 30%. Then, the soft sheath particles are dried at 60℃ for 2 hours and added to an extruder. The sheath extrusion temperature is set as follows: zone 1 temperature is 140℃, zone 2 temperature is 150℃, and die head temperature is 155℃. A semi-extrusion die is used, and the traction speed is controlled at 5m / min. After the sheath is formed, it is first rinsed with warm water and then with cold water. Finally, it is wound and shaped, with the winding tension controlled at 10N. After the cable is wound, it is placed for 24 hours to shape, resulting in a special soft power aluminum alloy cable.
[0031] Comparative Example 3: This comparative example illustrates the processing technology of a special flexible power aluminum alloy cable, including the following steps: Step s1: Add 100g of polyvinyl chloride resin (polyvinyl chloride resin product number: Zhongtai SG-5) and 3.5g of calcium-zinc stabilizer to a high-speed mixer and mix for 3 minutes at a temperature of 75℃ and a speed of 700r / min. Add 35mL of dioctyl terephthalate and 8mL of dioctyl adipate and continue stirring for 5 minutes. Add 10g of nitrile rubber (nitrile rubber is Lanzhou Petrochemical, model: N41E) and continue mixing for 4 minutes. Add 1.2g of lubricant (lubricant is a mixture of low-density polyethylene wax and stearic acid in a 2:1 ratio; low-density polyethylene wax is BASF, model: Luwax® A Powder), 0.3g of antioxidant (antioxidant model: Irganox 1010), and 20g of activated calcium carbonate (calcium carbonate is 1250 mesh activated calcium carbonate). Mix for 3 minutes and discharge to obtain the compound material. Step s2: Set the temperature of each section of the twin-screw extruder: section 1 of the die body 130℃, section 2 of the die body 140℃, section 3 of the die body 150℃, and the die head 165℃. Preheat for 30 minutes. Add the mixed material to the feed port of the extruder and adjust the screw speed to 25 r / min. After the extruded strip is cooled to room temperature in a cooling water tank, it is sent to a pelletizer to be pelletized (particle size 2mm). Collect the pellets and place them in an oven at 60℃ to dry for 30 minutes to obtain soft sheathed pellets. Step s3: Place the graphite crucible in the resistance furnace and preheat it at 300℃ for 30 minutes. Then, add 1000g of high-purity aluminum ingot (500g small pieces) to the graphite crucible and place it in the resistance furnace. Heat the crucible to 730℃ at a heating rate of 5℃ / min and hold it for 10 minutes. Turn on the argon gas cylinder and insert the argon gas tube 2cm below the surface of the molten aluminum. Adjust the argon gas flow rate to 0.5L / min and continue blowing argon for 5 minutes. Stop blowing argon and sprinkle 3g of refining agent (sodium-free refining agent for aluminum, model: HY-WJ1, particle size: 100 mesh) into the crucible. Stir with a graphite stirring rod for 5 minutes, let it stand for 3 minutes, and skim off the surface scum to obtain molten aluminum. Step s4: Stabilize the temperature of the molten aluminum at 740℃, sprinkle 30g of Al-Ti-B refining agent (5% Ti content, 1% B content, the remainder is Al, 5mm diameter) onto the surface of the molten aluminum, stir for 3 minutes, let stand for 3 minutes, skim off the surface scum, turn on the argon gas again at a flow rate of 0.3L / min, blow argon for 3 minutes, then adjust the temperature to 735℃ and hold for 2 minutes, then pour into a graphite mold, control the casting height at 10cm, let the mold cool naturally to room temperature, remove the surface oxide layer and burrs after cooling, and obtain the aluminum alloy ingot; Step s5: Cut the aluminum alloy ingot into φ12mm round bars with a length of 1000mm. Grind the surface with sandpaper, and then cold draw it using a wire drawing machine. Select a wire drawing die with progressively smaller sizes, with the die sizes being 12mm, 10mm, 8mm, 6mm, and 4mm respectively. Control the deformation amount in each pass to 15%, and the total deformation amount to reach 75%. The final wire diameter is φ4mm. After every two passes, wipe the surface of the wire with anhydrous ethanol. Place the cold-drawn wire into an annealing furnace, maintaining a gap (≥5mm) between the wires. Close the furnace door and heat it to 300℃ at a heating rate of 3℃ / min. Hold it at this temperature for 1.5h, during which argon gas with a flow rate of 0.2L / min is introduced. After annealing, cool it to room temperature with the furnace and grind the surface with sandpaper to obtain a soft aluminum alloy conductor. Step s6: Install the flexible aluminum alloy conductor on the pay-off frame, adjust the pay-off tension to be stable and without shaking, then start conductor preheating, controlling the temperature at 60℃. Add the insulating granules (Dow POE ENGAGE 8150 polyolefin elastomer) to the extruder hopper, using a three-stage extrusion temperature setting: zone 1 temperature 135℃, zone 2 temperature 145℃, and die head temperature 150℃. Adjust the die concentricity to ensure the insulation layer covers the conductor, controlling the traction speed at 6m / min. Cool the insulated wire core in a water-cooling bath at 20℃ to obtain the insulated wire core. Then, bring two insulated wire cores together, filling the gap with flexible filler rope (the flexible filler rope is made of polypropylene with a diameter of Φ3.0mm). Finally, apply polyester tape (the thickness of the polyester wrapping tape is 0mm) to the outer layer of the cable core. The soft sheath particles (0.05mm) are overlapped and wrapped, with an overlap rate of 30%. Then, the soft sheath particles are dried at 60℃ for 2 hours and added to an extruder. The sheath extrusion temperature is set as follows: zone 1 temperature is 140℃, zone 2 temperature is 150℃, and die head temperature is 155℃. A semi-extrusion die is used, and the traction speed is controlled at 5m / min. After the sheath is formed, it is first rinsed with warm water and then with cold water. Finally, it is wound and shaped, with the winding tension controlled at 10N. After the cable is wound, it is placed for 24 hours to shape, resulting in a special soft power aluminum alloy cable.
[0032] Performance testing: The special flexible power aluminum alloy cables of Examples 1-3 and Comparative Examples 1-3 were tested according to the following methods; Sheath tensile stress test: The test was conducted in accordance with GB / T 2951.11-2008 "General test methods for insulation and sheath materials of cables and optical cables - Part 11: General test methods for thickness and dimensional measurement and mechanical properties test". The specimen was dumbbell-shaped and the tensile rate was 50 mm / min.
[0033] Sheath elongation at break test: Similar to the tensile strength test, the elongation at break is recorded simultaneously.
[0034] Sheath bending resistance test: The test is conducted in accordance with GB / T 5023.2-2008 "PVC insulated cables with rated voltage of 450 / 750V and below - Part 2: Test methods", with a bending angle of 180° and a bending frequency of 10 times / min, until the sheath cracks.
[0035] Conductor resistivity test: The test shall be conducted in accordance with GB / T 3048.2-2007 "Test methods for electrical properties of wires and cables - Part 2: Test for resistivity of metallic materials", and the test temperature shall be 25℃.
[0036] Conductor bending breakage test: The test shall be conducted in accordance with GB / T 4909.5-2009 "Bare wire test method Part 5: Bending test repeated bending", with a bending angle of 180°, a bending radius of 5 times the conductor diameter, and a bending frequency of 8 times / min until the conductor breaks.
[0037] Low temperature bending test: The test is conducted in accordance with GB / T 2951.14-2008 "General test methods for insulation and sheath materials of cables and optical cables - Part 14: General test methods - Low temperature test". The cable is placed in a -15℃ constant temperature chamber for 1 hour. After taking it out, it is immediately bent 180° and the sheath and conductor are observed to see if cracks appear.
[0038] The test results are shown in Table 1: Table 1: Test Results Summary Table
[0039] Referring to Table 1, based on the comparison between Examples 1-3 and Comparative Examples 1-3, it can be seen that the special flexible power aluminum alloy cable has excellent conductivity, high flexibility and bending resistance, good mechanical strength and low temperature stability, which can meet the long-term reliable use requirements under frequent moving and bending conditions.
[0040] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0041] The above description is merely an example and illustration of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described or use similar methods to replace them, as long as they do not deviate from the invention or exceed the scope defined in this application, they should all fall within the protection scope of the present invention.
Claims
1. A processing technology for a special flexible power aluminum alloy cable, characterized in that, Includes the following steps: The flexible aluminum alloy conductor is installed on the wire feeding frame, then the conductor preheating is turned on. Insulating particles are added to the extruder hopper, and the concentricity of the die is adjusted to ensure that the insulation layer covers the conductor. After cooling, the insulated wire core is obtained. Then, the two insulated wire cores are brought together and flexible filler rope is filled into the gap. Then, polyester tape is used to wrap the outer layer of the cable core in an overlapping manner. After the flexible sheath particles are dried, they are added to the extruder. After the sheath is formed, it is first warm water and then cold water. Finally, it is wound and shaped to obtain a special flexible power aluminum alloy cable. The flexible filling rope is made of polypropylene and has a diameter of Φ3.0mm; the polyester wrapping tape has a thickness of 0.05mm. The soft sheath particles are prepared by the following steps: Step a1: Add maleic anhydride and n-octadecylamine to a three-necked flask, add toluene using a syringe, stir the reaction, add the solution after reaction to ice-cold methanol and stir, collect the precipitate, filter, and dry to obtain octadecylmaleamic acid; Step a2: Add octadecyl maleamic acid and anhydrous sodium acetate to a three-necked flask, add toluene and acetic anhydride respectively using a syringe, stir the reaction, cool, and drop the reaction solution into ice-cold methanol and stir to produce a precipitate. Filter and dry to obtain N-octadecyl maleimide. Step a3: Add ethylene-vinyl acetate copolymer, N-octadecyl maleimide and benzoyl peroxide to a three-necked flask, add toluene with a syringe, stir, heat and continue stirring to react, add the reacted solution dropwise to ice-cold methanol and stir to produce a precipitate, filter, wash, and then dry to obtain a high-performance functional modifier. Step a4: Add polyvinyl chloride resin and calcium-zinc stabilizer to a high-speed mixer and mix. Add dioctyl terephthalate and dioctyl adipate and continue stirring and mixing. Add nitrile rubber and high-performance functional modifier and continue mixing. Add lubricant, antioxidant and activated calcium carbonate, mix, and discharge to obtain the compound material. Step a5: Set the temperature of each section of the twin-screw extruder, preheat it, add the mixed material to the extruder feed inlet, cool the extruded strip, send it to the pelletizer to pelletize, dry it, and obtain soft-coated pellets.
2. The processing technology of a special flexible power aluminum alloy cable according to claim 1, characterized in that, The ratio of maleic anhydride, n-octadecylamine, toluene, and glacial methanol used in step a1 is 0.05-0.10 mol: 0.04-0.08 mol: 100-200 mL: 1-2 L.
3. The processing technology of a special flexible power aluminum alloy cable according to claim 1, characterized in that, The ratio of octadecyl maleamic acid, anhydrous sodium acetate, toluene, acetic anhydride and icy methanol used in step a2 is 0.04-0.08 mol: 3-6 g: 100-200 mL: 0.15-0.30 mol: 500-1000 mL.
4. The processing technology of a special flexible power aluminum alloy cable according to claim 1, characterized in that, The ratio of the amounts of ethylene-vinyl acetate copolymer, N-octadecyl maleimide, benzoyl peroxide, toluene, and glacial methanol in step a3 is 0.5-1.0g: 0.8-1.6g: 0.005-0.02g: 25-50mL: 500-1000mL.
5. The processing technology of a special flexible power aluminum alloy cable according to claim 1, characterized in that, In step a4, the ratio of polyvinyl chloride resin, calcium-zinc stabilizer, dioctyl terephthalate, dioctyl adipate, nitrile rubber, high-performance functional modifier, lubricant, antioxidant, and activated calcium carbonate is 100-200g: 3.5-7.0g: 35-70mL: 8-16mL: 10-20g: 3-6g: 1.2-2.4g: 0.3-0.6g: 20-40g; the lubricant is a mixture of low-density polyethylene wax and stearic acid in a ratio of 2:1; and the calcium carbonate is 1250-mesh activated calcium carbonate.
6. The processing technology of a special flexible power aluminum alloy cable according to claim 1, characterized in that, The flexible aluminum alloy conductor is prepared by the following steps: Step b1: Place the graphite crucible in the resistance furnace for preheating, then add the high-purity aluminum ingot into the graphite crucible, send it into the resistance furnace, continuously blow argon, sprinkle the refining agent into it, stir, let it stand, skim off the surface scum, and obtain aluminum liquid. Step b2: Stabilize the temperature of the molten aluminum at 740℃, add the Al-Zr master alloy to the molten aluminum, stir, let stand, then add the Al-RE rare earth master alloy, stir, let stand, sprinkle the Al-Ti-B refining agent on the surface of the molten aluminum, stir, let stand, skim off the surface scum, blow argon, then adjust the temperature to 735℃, keep it at the temperature, then pour it into a graphite mold, cool the mold, remove the surface oxide layer and burrs, and obtain the aluminum alloy ingot; Step b3: Cut the aluminum alloy ingot, grind the surface, and then cold draw it. Use a gradually shrinking wire drawing die to put the cold-drawn wire into an annealing furnace for heating, then cool it, grind the surface, and obtain a soft aluminum alloy conductor.
7. The processing technology of a special flexible power aluminum alloy cable according to claim 6, characterized in that, In step b1, the ratio of high-purity aluminum ingot to refining agent is 1000-2000g: 3-5g; in step b2, the ratio of Al-Zr master alloy, Al-RE rare earth master alloy and Al-Ti-B refining agent is 50-100g: 20-40g: 30-60g.
8. The processing technology of a special flexible power aluminum alloy cable according to claim 6, characterized in that, The high-purity aluminum ingot in step b1 is in 500g pieces; the refining agent in step b1 is a sodium-free refining agent for aluminum with a particle size of 100-200 mesh; the Al-Zr master alloy, Al-RE rare earth master alloy, and Al-Ti-B refining agent in step b2 are particles with a diameter of 5-10mm; the Al-Zr master alloy has a Zr content of 10% and the remainder is Al; the Al-RE rare earth master alloy has a La and Ce mixed rare earth content of 20%, wherein the mass ratio of La to Ce is 1:1 and the remainder is Al; the Al-Ti-B refining agent has a Ti content of 5%, a B content of 1%, and the remainder is Al.